2014
DOI: 10.1021/am503633t
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Dielectric Loss of Polymer Composites from Coating Carbon Nanotubes with a Cross-Linked Silsesquioxane Shell through Free-Radical Polymerization

Abstract: We report a synthetic strategy for coating multiwalled carbon nanotubes (MWCNTs) with cross-linked octa-methacrylate-polyhedral oligomeric silsesquioxane (MA-POSS) by direct, in situ free-radical polymerization in a controlled manner. This strategy resulted in a core-shell structure with an MWCNT center. The shell thickness could be varied from ∼ 7 nm to 40 nm by choosing different initiators, solvents, and weight ratios of MWCNT and octa-MA-POSS. Coated MWCNT hybrids had controlled electrical performance depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Recently, the functionalization of MWCNTs with POSS reagents has been found to significantly improve the mechanical, thermal and electrical properties of MWCNT-polymer nanocomposites [4][5][6][7][8]. Li et al [4] reported an improved dispersion of MWCNTs throughout a poly(L-lactide) polymer after POSS-treatment of nanotubes, resulting in a higher tensile modulus, yield strength and electromagnetic interference shielding effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the functionalization of MWCNTs with POSS reagents has been found to significantly improve the mechanical, thermal and electrical properties of MWCNT-polymer nanocomposites [4][5][6][7][8]. Li et al [4] reported an improved dispersion of MWCNTs throughout a poly(L-lactide) polymer after POSS-treatment of nanotubes, resulting in a higher tensile modulus, yield strength and electromagnetic interference shielding effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [4] reported an improved dispersion of MWCNTs throughout a poly(L-lactide) polymer after POSS-treatment of nanotubes, resulting in a higher tensile modulus, yield strength and electromagnetic interference shielding effectiveness. Sun et al [5] studied the effect of POSS-coating of MWCNTs on the electrical properties of MWCNTpoly(vinylidene fluoride) composites. The dielectric properties of composite was enhanced by controlling the thickness of the POSS layer.…”
Section: Introductionmentioning
confidence: 99%
“…POSS molecules have a comparable size with the segments of polymer chains and can react with polymers with good solubility in many solvents. Therefore, dielectric polymer nanocomposites using POSS as a nanofiller have attracted attention for high voltage applications in the engineering dielectric and electrical insulation fields …”
Section: Advanced Applicationsmentioning
confidence: 99%
“…Therefore, dielectric polymer nanocomposites using POSS as a nanofiller have attracted attention for high voltage applications in the engineering dielectric and electrical insulation fields. [72,73] Reactive POSS can be used to improve the dielectric properties of epoxy resin for high voltage insulation applications. For example, octa-aminophenyl POSS (OASQ) or glycidyl-POSS are commonly incorporated into epoxy to form hybrid materials with enhanced electrical properties.…”
Section: Enhancement Of Electrical Properties Of Polymersmentioning
confidence: 99%
“…Moreover, the combination of a large surface area and a high aspect ratio with attractive van der Waal interaction forces in CNTs makes them aggregate to bundles; thus, they are often difficult to mix with polymers. 35 Analyzing the dielectric studies of the MWCNT-epoxy composite filled with low weight percentage of the MWCNT as filler in composite materials at different temperatures and frequencies is the aim of this work. The effect of temperature on the dielectric properties of the prepared specimens at different frequencies is observed.…”
Section: Introductionmentioning
confidence: 99%